THE RELATIONSHIP BETWEEN THE MECHANICAL PARAMETERS IN THE TAKE-OFF OF A VAULT AND THE DROP JUMP ABILITY - Yoshie Motoshima; Junichi Kitagawa; Akira Maeda (Science of Gymnastics Journal)
In the vault in gymnastics, the take-off motion is important to the success of the vault and to perform more difficult vaults. Vaulting ability has been studied by motion analysis, but this method is not effective for easy evaluation. Therefore, the purpose of this study was to investigate the relationship between the mechanical parameters in the take-off of a vault and the drop jump ability, by focusing on the rebound drop jump index (RDJ index) calculated from the two variables of contact time and flight time. Male gymnasts performed the Kasamatsu vault, and their vaulting motion was captured using the 3-dimensional optical motion capture system MAC3D. In addition, they performed a drop jump from a height of 0.4 m without arm swing under two conditions (vault board and non-spring floor), and the RDJ index was calculated. As a result of calculating the regression equation for estimating the vertical impulse of the Kasamatsu vault by using the RDJ index of the drop jump, a significant regression equation was obtained in the RDJ index of the drop jump on the vault board (y = 0.290x + 5.368, p < 0.05). This result suggests the possibility that the vertical impulse of the take-off on the vault board can be evaluated by measurement under conditions whose characteristics are similar to those of actual vaulting, such as a drop jump on a vault board, in high-level gymnasts.